Metode Revised Universal Soil Loss Equation (RUSLE): Pendugaan Potensi Erosi, Sebuah Analisis Google Earth Engine - Lalu Auliya Akraboelittaqwa; M Said Ramdlan (Indonesian Journal of Engineering (IJE), 2023)
Abstrak Penelitian ini bertujuan untuk menghitung tingkat erosi yang terjadi di DAS Meninting dan upaya yang perlu dilakukan untuk meningkatkan produktivitas lahan guna menjaga kualitas lingkungan serta menghilangkan dampak negatif seperti erosi, sedimentasi serta banjir. Semua data diolah dengan javascript pada platform GEE. Hasil analisis terdapat kehilangan tanah didominasi di bagian hulu DAS. Selain itu, terdapat kehilangan tanah berdasarkan data citra yang terkumpul dan dipanggil di cloud menggunakan platform GEE, yaitu 699.149 ton/ha/tahun. Penanggualan yang dapat dilakukan yaitu dengan metode konservasi dengan metode penanaman menurut garis kontur.Abstract. The purpose of the study is to calculate the erosion rates of Meninting watershed and measures to improve the land productivity to eradicate the negative impacts such as erosion, sedimentation, and flood. Data is processed using JavaScript on the GEE platform. The results indicate the magnitude of the erosion rate in the Meninting watershed can be seen in the image below. It is indicated that with the applied method, soil loss is dominated in the upstream of the watershed. It is estimated that the loss of land using image data collected and retrieved in the cloud using the GEE platform is 699,149 tons/ha/year. one of mitigation measures is using the conservation method with the method of planting according to contour lines.